Observation of an exotic narrow doubly charmed tetraquark - Aaij, R.; Abdelmotteleb, A. S. W.; Abellán Beteta, C.; Abudinen Gallego, F. J.; Ackernley, T.; Adeva, B.; Adinolfi, M.; Afsharnia, H.; Agapopoulou, C.; Aidala, C. A.; Aiola, S.; Ajaltouni, Z.; et al. (Nature physics, 2022)
Conventional, hadronic matter consists of baryons and mesons made of three quarks and a quark–antiquark pair, respectively 1 , 2 . Here, we report the observation of a hadronic state containing four quarks in the Large Hadron Collider beauty experiment. This so-called tetraquark contains two charm quarks, a u ¯ and a d ¯ quark. This exotic state has a mass of approximately 3,875 MeV and manifests as a narrow peak in the mass spectrum of D 0 D 0 π + mesons just below the D *+ D 0 mass threshold. The near-threshold mass together with the narrow width reveals the resonance nature of the state. The LHCb Collaboration reports the observation of an exotic, narrow, tetraquark state that contains two charm quarks, an up antiquark and a down antiquark.